A simple method to widen the IF bandwidth of a high frequency SIS mixer - Tan, B; Yassin, G; Grimes, P (2013)
In this paper, we describe a simple method for widening the instantaneous frequency (IF) bandwidth of a high frequency superconductor-insulator-superconductor (SIS) mixer. This method requires only a standard PCB technology, without incurring any difficulties or complication in altering the tunnel junction fabrication. It involves the use of a simple multi-stage IF transformer to match the dynamic output impedance of the SIS mixer to a 50 Ω load over a wide IF bandwidth. We use an existing 650 GHz SIS mixer chip as an example to illustrate the methodology of the IF transformer design. In this example, we show how we widen the IF bandwidth of the mixer to operate over 4–12 GHz bandwidth using this simple impedance matching method.